2021
DOI: 10.1038/s41582-021-00509-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of migraine in ten steps

Abstract: Migraine is a disabling primary headache disorder that directly affects more than one billion people worldwide. Despite its widespread prevalence, migraine remains under-diagnosed and under-treated. To support clinical decision-making, we convened a European panel of experts to develop a ten-step approach to the diagnosis and management of migraine. Each step was established by expert consensus and supported by a review of current literature, and the Consensus Statement is endorsed by the European Headache Fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
210
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 271 publications
(303 citation statements)
references
References 134 publications
1
210
0
3
Order By: Relevance
“…Neuroimaging is not an essential part of headache investigations and should be reserved for those with red flags indicating secondary headaches [ 12 , 25 ]. Several studies have shown that neuroimaging is routinely ordered despite a typical headache history and normal clinical examination [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Neuroimaging is not an essential part of headache investigations and should be reserved for those with red flags indicating secondary headaches [ 12 , 25 ]. Several studies have shown that neuroimaging is routinely ordered despite a typical headache history and normal clinical examination [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective treatments exist for the most common primary headache disorders, migraine and tension-type headache [ 12 , 29 ]. About one in three GPs reported that they had good knowledge about migraine and TTH, and > 96% reported good or medium knowledge about migraine and TTH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations